RANCANG BANGUN SISTEM PELAYANAN MASYARAKAT DI KANTOR DESA SANGTANDUNG BERBASIS WEBSITE - Yunita Sahar (Jurnal Riset Sistem Informasi, 2024)
This research aims to create a Web-Based Community Service System Design in Sangtandung Village. The system development method used in the research is the waterfall method with a system  testing technique, namely black box. In its design,   this  service  system   application  uses  the  UML  (Unified  Modeling Language)  development  method which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. Database logic design using MySQL and system interface. The software used in designing and implementing the system  uses XAMPP as a web server, PhpMySQL as a database, Visual Studio as a web design editor and HTML as a website design editor. Design and development of a web-based community service system in Sangtandung Village including information pages, population data pages, history pages and criticism pages. The application has been tested so that an application that runs well is obtained. And help provide good community services.